2017
DOI: 10.1038/s41467-017-02049-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T5 tail tube structure suggests a trigger mechanism for Siphoviridae DNA ejection

Abstract: The vast majority of phages, bacterial viruses, possess a tail ensuring host recognition, cell wall perforation and safe viral DNA transfer from the capsid to the host cytoplasm. Long flexible tails are formed from the tail tube protein (TTP) polymerised as hexameric rings around and stacked along the tape measure protein (TMP). Here, we report the crystal structure of T5 TTP pb6 at 2.2 Å resolution. Pb6 is unusual in forming a trimeric ring, although structure analysis reveals homology with all classical TTPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(137 citation statements)
references
References 58 publications
4
130
0
3
Order By: Relevance
“…Other studies have revealed no apparent conformational change in the tail tube associated with the infection process in siphoviruses [32]. Even in the myoviruses, tail contraction itself is not the signal that leads to ejection [11,35]. Our observation of TMP α-helices associated with Tal resolves this conundrum: upon release by Tal, the TMP α-helices might act as a "pull cord" that drags the DNA along during injection ( Fig 6C).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Other studies have revealed no apparent conformational change in the tail tube associated with the infection process in siphoviruses [32]. Even in the myoviruses, tail contraction itself is not the signal that leads to ejection [11,35]. Our observation of TMP α-helices associated with Tal resolves this conundrum: upon release by Tal, the TMP α-helices might act as a "pull cord" that drags the DNA along during injection ( Fig 6C).…”
Section: Discussionmentioning
confidence: 47%
“…This luminal β-sheet contains an extended insertion loop between β2 and β3 (the "stacking loop") that reaches across the �3 Å space that separates tail rings and inserts into a pocket between two subunits in the adjacent ring ( Fig 3A). The equivalent loop in the major tail proteins of phages λ, T5 and SPP1 was shown to play an essential role in tail polymerization [33][34][35].…”
Section: The Major Tail Protein (Mtp Gp53)mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments such as those presented herein will contribute to extending the applicabilityo fM AS ssNMRt op roteins of increasing size, complexity and biological interest. Regions with significant Dd valuesare highlighted in red, and plotted onto the structural model of the full-length pb6tubes [30] (panel C). ChemPhysChem 2017ChemPhysChem , 18,2697ChemPhysChem -2703 www.chemphyschem.org 2017 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim…”
Section: Discussionmentioning
confidence: 99%
“…Af irst observation is that the chemical shifts are, overall, very similar,e stablishing that this domain, as part of the assembled tube, retains its conformation. The regionsw ith significant differences in chemical shifts are plotted onto as tructural model of the pb6 tail tubes [30] in Figure6.T hese parts are located in close proximity to the remainder of the protein, that is, where the Ig-like domain contacts the core of the tail tube, as one expects from the structuralm odel.W ea re currently extending the assignmentso fp b6 to the remaining 374 residues,i no rder to characterize the structure, interactions and dynamics of these assemblies in detail. The approaches presented herein will be a key elementinp ursuing thesestudies.…”
Section: Insight Into the 504 Kda Bacteriophage T5 Tube Proteinmentioning
confidence: 99%